Functional and structural correlates of abnormal involuntary movements in psychosis risk and first episode psychosis - Kindler, Jochen; Michel, Chantal; Schultze-Lutter, Frauke; Felber, Gwendolin; Hauf, Martinus; Schimmelmann, Benno G.; Kaess, Michael; Hubl, Daniela; Walther, Sebastian (Schizophrenia research, 2019)
Background - Abnormal involuntary movements (AIM) may occur throughout the course of psychosis. While AIM are thought to indicate striatal abnormalities, the functional and structural correlates of increased AIM remain elusive. Here, we examined the prevalence of AIM in patients with clinical high risk for psychosis (CHR), first episode psychosis (FEP) and clinical controls (CC). Furthermore, we tested the association of AIM with regional cerebral blood flow (rCBF), grey matter volume (GMV), and premorbid IQ. - Methods - We conducted a video-based analysis of AIM in patients with CHR (n=45), FEP (n=10) and CC (n=39), recruited in the Early Detection and Intervention Center, Bern. Premorbid intelligence was evaluated using the Peabody Picture Vocabulary test. Additionally, arterial spin labeling MRIs and structural MRIs were acquired in a subgroup of the sample to investigate the association of AIM with rCBF and GMV. - Results - Higher total AIM scores were detected in CHR (p=0.02) and FEP (p=0.04) as compared to CC. When separated for different muscle groups, lips and perioral movements were significantly increased in CHR patients as compared to CC (p=0.009). AIM scores correlated positively with rCBF in the premotor cortex, Brodmann area 6 (p<0.05, FWE corrected). Negative correlations were found between AIM and GMV of the corresponding caudal middle frontal gyrus (p=0.04, FWE corrected) and premorbid intelligence (p=0.02). - Conclusions - AIM were more frequent in the psychosis spectrum than in clinical controls. Neuroimaging findings indicate an involvement of cortical motor areas in abnormal motor behavior, instead of pure basal ganglia pathology.